Anti-avoidance rules against international tax planning A classification - Johansson, Åsa (OECD Publishing, 2017)
This paper describes the main anti-avoidance rules against international tax planning by multinational enterprises in OECD and G20 countries. Building on this information and on previous classification efforts in the literature, a new classification of anti-avoidance strength is compiled. It takes into account five key dimensions of anti-avoidance: (i) transfer price rules and documentation requirements; (ii) rules on interest deductibility such as thin capitalisation and interest-to-earnings rules to prevent the manipulation of debt location; (iii) controlled foreign company (CFC) rules; (iv) general anti-avoidance rules (GAARs); and (v) withholding taxes on interest payments, royalties and dividends, taking into account bilateral tax treaties. The classification is based on a simple framework aiming to capture the main features of anti-avoidance rules in a harmonised way across countries, although it inevitably leaves aside certain country-specific characteristics as well as the enforcement of existing rules. The empirical analysis in Johansson et al., (2016), which is based on this classification, suggests that strong anti-avoidance rules can reduce profit shifting
Keywords: Taxation; Economics